Komunikasi dalam Berbagai Bahasa dalam Interaksi Sosial Mahasiswa Teologi di Sekolah Tinggi Teologi di Jakarta - Marudut Bernadtua Simanjuntak (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2022)
This study aims to study communication in various languages in the social interactions of Theology students at the Theological College in Jakarta. The focus of this research is to explore how students can communicate in various languages, namely Indonesian, English, and regional languages (Javanese, Batak, Banjar, and Sundanese). In addition, this study also aims to identify how students and the community can establish active and comfortable communication in conveying ideas and ideas. Lastly, this research will study the views of the people in Jakarta, especially the people on the outskirts of Jakarta such as the borders of Bekasi, Depok, Tangerang, and Bogor Cities, towards the presence of Christian Theology students in contributing to society. This research method involves collecting data through observation, interviews, and document analysis. The data obtained will be analyzed critically to gain a deep understanding of student's communication skills in various languages, their efforts to build active and comfortable communication, as well as public perceptions of the role and contribution of Christian Theology students in Jakarta. The results of this research are expected to provide valuable insights into the development of Theology education, cross-cultural understanding, and the social contribution of Theology students in society. Through a better understanding of the importance of communication in multiple languages in the social interactions of Theology students, steps can be taken to improve the quality of education, communication skills, and social contributions of future Theology students. In this context, cooperation between educational institutions, the community, and the government in Jakarta is very important to create a conducive environment for the development of theology students' communication skills in various languages and establish harmonious relations between students and the community.